Adherence to mass drug administration and environmental factors related to lymphatic filariasis incidence: A case-control study in endemic area, Papua, Indonesia - Wayangkau, Erich C.; Budiyono, Budiyono; Raharjo, Mursid; Martini, Martini (Narra Sains Indonesia, 2025)
Papua has the highest number of lymphatic filariasis cases in Indonesia. Despite the implementation of mass drug administration (MDA), adherence to MDA remains low in this region. The aim of this study was to evaluate the influence of adherence to MDA and environmental factors on the incidence of lymphatic filariasis. The study was conducted in 11 areas in Sarmi Regency, Papua, in 2024. This case-control study included 135 respondents (45 cases and 90 controls) selected through a proportional random sampling method. Data were collected via structured interviews, observations, and medical record reviews. Data analysis was performed using logistic regression with the backward likelihood ratio method to identify risk factors. The study revealed that male (aOR: 4.88; 95%CI: 1.39–17.06; p=0.013), age ≥40 years (aOR: 4.65; 95%CI: 2.26–7.00; p=0.002), low education level (aOR: 0.24; 95%CI: 0.07–0.84; p=0.025), and income below the regional minimum wage (aOR: 15.66; 95%CI: 1.84–30.26; p=0.012) were significant risk factors for lymphatic filariasis incidence. Non-consumption of complete antifilarial drugs (aOR: 3.24; 95%CI: 1.00–10.50; p=0.050), not taking antifilarial drugs at the recommended time (aOR: 7.36; 95%CI: 1.99–27.23; p=0.003), and delayed consumption of antifilarial drugs (aOR: 3.73; 95%CI: 1.09–12.73; p=0.036) were adherence-related factors associated with an increased risk. Furthermore, not wearing long-sleeved clothing at night (aOR: 6.73; 95%CI: 1.81–24.94; p=0.004) was significantly associated with lymphatic filariasis incidence. The dimensions of MDA medication adherence, including the consumption of preventive antifilarial drugs, night-time dosing, and immediate consumption of antifilarial drugs after distribution, were associated with lymphatic filariasis incidence in Papua. This study suggests that MDA programs against filariasis in endemic areas need to be supported by adherence-focused interventions to enhance the effectiveness of prevention efforts.